Observation of self-organized FRC formation in a collisional-merging experiment. (16th August 2021) - Asai, Tomohiko; Kobayashi, Daichi; Seki, Taichi; Tamura, Yasuaki; Watanabe, Tatsuhiro; Sahara, Naoto; Takahashi, Tsutomu; Morelli, Jordan; Gota, Hiroshi; Roche, Thomas; Magee, Richard; Binderbauer, Michl; et al.
Abstract: Self-organized field-reversed configuration (FRC)-like formation was observed after the super-sonic/Alfvénic collisional merging of two FRCs in the FAT-CM device at Nihon University. In this experiment, two FRCs were generated initially in two separate field-reversed theta-pinch type formation regions. Those two formation regions are coaxially connected to opposite ends of a cylindrical confinement chamber. The formed FRCs are oppositely-translated and collide in the middle of the confinement chamber at super-sonic/Alfvénic velocity. During the collision, the merged plasmoid experiences destructive disturbance and loses its fast toroidal flow and characteristic FRC property of having a field-reversed magnetic configuration to become a magnetized plasma without ordered structure. After this dynamic collision, a magnetic configuration of FRC with fast toroidal rotation is self-organized within a few tens of microseconds. This observation indicates robustness of the extremely high-beta, simple magnetic configuration.